Digitalization of public finance auditing as a tool for ensuring accountability in public governance during emergencies and war - Tereshchenko, Dina; Kruhlov, Vitalii; Bodnar, Kateryna (Theory and Practice of Public Administration, 2024)
The article examines the potential of digital technologies in transforming the system of public finance auditing under conditions of emergencies and prolonged wartime uncertainty. It substantiates the need to transition from traditional retrospective audit methods to digital approaches, including continuous real-time auditing and big data analysis. The authors emphasize that these tools significantly enhance the efficiency, transparency, and accountability of budget resource management in crisis situations. The study focuses on three key aspects. The first section explores the theoretical and methodological foundations of audit digitalization, highlighting its role in strengthening control over public finances. The second section presents a conceptual model of digital auditing, which involves integrating innovative technologies such as data analysis algorithms, blockchain, business intelligence (BI) systems, and visualization tools. The third section investigates the potential benefits of digital auditing, including proactive risk management, mitigation of corruption risks, and strengthening citizens’ trust in government. The research is based on a systemic approach that considers auditing as a dynamic component of public governance. Methods of analysis, synthesis, comparative analysis, and modeling were used to evaluate international practices and adapt best practices to the Ukrainian context. The informational base comprises analytical materials from international organizations (INTOSAI, OECD), data from Ukrainian government institutions, and scientific studies. Key findings demonstrate that digital technologies have the potential to enable a transformative shift in the audit system, improving its speed, accuracy, and flexibility. The authors stress that the effective implementation of digital auditing requires political will, reform of the regulatory framework, development of digital competencies among public officials, and active engagement of civil society. The proposed conceptual model of audit digitalization has the potential to become a cornerstone of Ukraine’s post-war transformation, ensuring transparency, accountability, and efficient use of public funds.